The mobility-security nexus and the making of order : an interdisciplinary and historicizing intervention - Distler, Werner; Hein-Kircher, Heidi (2022)
"The book explores the complex, multi-directional connections of the "mobility/security nexus" in the re-ordering of states, empires, and markets in historical perspective. Contributing to a vivid academic debate, the book offers in-depth studies on how mobility and security interplay in the emergence of order beyond the modern state. While mobilities studies, migration studies and critical security studies have focused on particular aspects of this relationship, such as the construction of mobility as a political threat or the role of infrastructure and security, we still lack comprehensive conceptual frameworks to grasp the mobility/security nexus and its role in social, political, and economic orders. With authors drawn from sociology, International Relations, and various historical disciplines, this transdisciplinary volume historicizes the mobility-security nexus for the first time. In answering calls for more studies that are both empirical and have historical depth, the book presents substantial case studies on the nexus, ranging from the late Middle Ages right up to the present-day, with examples from the British Empire, the Russian Empire, the Habsburg Empire, Papua New Guinea, Rome in the 1980s or the European Union today. By doing so, the volume conceptualizes the mobility/security nexus from a new, innovative perspective and, further, highlights it as a prominent driving force for society and state development in history. This book will be of much interest to researchers and students of critical security studies, mobility studies, sociology, history and political science